Florigen and anti-florigen – a systemic mechanism for coordinating growth and termination in flowering plants - Lifschitz, Eliezer; Ayre, Brian G.; Eshed, Yuval (Frontiers in Plant Science, 2014)
Genetic studies in Arabidopsis established FLOWERING LOCUS T (FT) as a key flower-promoting gene in photoperiodic systems. Grafting experiments established unequivocal one-to-one relations between SFT (SINGLE FLOWER TRUSS), a tomato homolog of FT, and the hypothetical florigen, in all flowering plants. Additional studies of SFT and SP (SELF PRUNING, homolog of TFL1), two antagonistic genes regulating the architecture of the sympodial shoot system, have suggested that transition to flowering in the day-neutral and perennial tomato is synonymous with ‘termination’. Dosage manipulation of its endogenous and mobile, graft-transmissible levels demonstrated that florigen regulates termination and transition to flowering in an SP-dependent manner and, by the same token, that high florigen levels induce growth arrest and termination in meristems across the tomato shoot system. It was thus proposed that growth balances, and consequently the patterning of the shoot systems in all plants, are mediated by endogenous, meristem-specific SFT/SP ratios, and that shifts to termination by elevated SFT/SP ratios are triggered by mobile florigen. Florigen is a universal growth plant hormone inherently checked by a complementary antagonistic systemic system. Thus, an examination of the endogenous functions of FT-like genes, or of the systemic roles of the mobile florigen in any plant species, that fails to pay careful attention to the balancing antagonistic systems, or to consider its functions in day-neutral or perennial plants, would be incomplete.